ENHANCING STATISTICAL UNDERSTANDING: A COMPARATIVE EFFECTIVENESS ANALYSIS OF YOUTUBE AND E-MODULE IN SOCIAL SCIENCES: MENDALAMI STATISTIKA: ANALISIS PERBANDINGAN EFEKTIVITAS MEDIA PEMBELAJARAN YOUTUBE DAN E-MODUL PADA RUMPUN ILMU SOSIAL - Puspa Nur Afifah; Rusmiyati (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
This study aimed to test the effectiveness of using YouTube and e-modules for statistics learning for social science students enrolled in statistics courses. Statistics is often considered an abstract and difficult subject to understand, which can trigger anxiety and reduce students’ learning motivation. A total of 31 students of the Islamic community development study program at UIN Sultan Maulana Hasanuddin participated in this study. Students were divided into one group that underwent two learning sessions: first, they studied frequency distribution material with YouTube learning media (audiovisual), and second, central measurement with e-module learning media (text-based), with a comparative quantitative approach evaluated through pretest and posttest. The results showed that both YouTube and e-modules were equally effective in improving students’ understanding of statistics. However, 84% of students who used YouTube showed a significant increase in understanding, while only 68% showed an increase after using the e-module. The average increase in scores with YouTube was 13.81 points, higher than 4.77 points on the e-module. The paired sample t-test indicated that YouTube was significantly more effective than the e-module, with a p-value < 0.05. YouTube’s advantages mainly lie in its visual and interactive features that help facilitate the understanding of abstract concepts in statistics. This study recommends integrating YouTube and e-modules to optimize statistics learning outcomes, especially in the social sciences.